Development of Assessment Instruments for Tennis Aptitude Tests Using Tonnis Game Methods for Elementary School Students - Anggarkusuma, Rosdyaningsih; Waluya, Budi; Khumaedi, Muhammad (Journal of Research and Educational Research Evaluation, 2018)
The current assessment instrument cannot be used to assess objective tennis talent for student in primary school. The aims of this research is to develop the assessment of tennis talent of the primary school students intenship with standardize. The method of this research was used research development with four steps development. The contents validity was analyzed by experts using Aiken's formula, the reliability was analyzed by the experts using Two way Anova and re-analyzed using the Hoyt formula. The construct validity was analyzed using exploratory factor analysis and reliability was analyse using Alpha Cronbach. The result of the validity of the content shows that there was thirty grains which have value > 0.3 with the total percentage of feasibility of 87% means the soft skill assessment instrument was feasible to be used, the result of the reliability based on the expert's test shows the value of 0.82 which means each rater agreed in judging. The KMO results on the instrument test in the Field shows a value of 0.779, MSA> 0.5 and Bartlett's test significance of 0.000 this means data was eligible for further analysis. The exploratory factor analysis shows nine factors from 30 statement items. The value of factor loading on each item that existed on each factor is > 0.3 which signify the whole item was valid. Based on the reliability test using Alpha Cronbach obtained value of 0.985 so that the instrument is reliable.The conclusion shows the assessment of tennis aptitude tests for elementary school students that are developed is valid, reliable and worthy to use. This research can be useful for PJOK teachers and tennis trainers as an effort to find potential athletes for tennis.